Cytokine gene expression in response to Haemonchus placei infections in Nelore cattle - Zaros, L. G.; Bricarello, P. A. [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP]; Rocha, R. A. [UNESP]; Kooyman, F. N. J.; De Vries, E.; Coutinho, L. L. (Elsevier B.V., 2010)
This study aimed to evaluate the expression of a subset of cytokine genes in response to Haemonchus placei infections in Nelore cattle presenting different degrees of resistance to natural infections. One hundred weaned bulls, initially 11-12 months old, were evaluated and kept on the same pasture. Faecal and blood samples were collected for parasitological and immunological assays. The seven most resistant and the eight most susceptible animals were selected based on nematode faecal egg counts (FEC) and worm burden. Serum was collected to measure antibody titres, and abomasum and abomasal lymph node tissue samples were collected to analyse the expression of a subset of cytokine genes (IL-2, IL-4, IL-8, IL-12p35, IL-13, TNF-alpha, IFN-gamma, MCP-1, MCP-2, MUC-1) using real-time RT-PCR. Mast cells, eosinophils and globule leukocytes in the abomasal mucosa were enumerated, and IgA levels in the mucus were assessed. Gene expression analysis in the abomasal tissue indicated that IL-4 and IL-13 (T(H)2 cytokines) were up-regulated in the resistant group, whereas TNF-alpha (T(H)1/T(H)2 cytokine) was up-regulated in the susceptible group. In abomasal lymph nodes, IL-4 and IFN-gamma were up-regulated in the resistant and susceptible groups, respectively. In the resistant group, serum IgG1 levels were higher against antigens of H. placei infective larvae on days 14, 42, 70 and 84 and against antigens of H. placei adults on day 84 (P < 0.05). The resistant group had higher mast cell counts in the abomasal mucosa than the susceptible group (P < 0.05). These results indicate a protective T(H)2-mediated immune response against H. placei in the resistant group and a less protective T(H)1 response in the susceptible group. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Cytokines; Gene expression; Haemonchus; Immunoglobulins; Nelore breed; Resistance